Level of Active Lifestyle and Exercise Approach among Sports-Active Female Students of The University of Sarajevo during the Covid-19 Pandemic - Izet Bajramovic; Srdjan Redzepagic; Dusko Bjelica; Dragan Krivokapic; Eldin Jeleskovic; Slavenko Likic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
Closure of all educational institutions as well as various facilities for sports and recreation, due to the COVID-19 pandemic and the adoption of social movement restrictions, impaired the possibility of maintaining healthy living habits of the student population. The aim of this research was to identify changes in healthy living habits and exercise approach of sports-active female students, caused by the COVID-19 pandemic, in order to prevent possible harmful consequences on their physical fitness level. The sample of respondents were female students (n=110; 22.1±1.69 years of age), who stated that they were active members of various sports clubs during the period before the COVID-19 pandemic. A survey questionnaire was used in the study to assess a healthy lifestyle. The analysis of the obtained answers within the survey questionnaire was evaluated in relation to the percentage values of the frequencies of these answers. The results indicate that the level of regular and planned physical exercise of sports-active female students decreased by 41.7% during the COVID-19 pandemic, and that the level of their physical condition decreased by 38.2%. Changes in eating habits were recorded in 50% of female sportsactive female students, while 36.3% of them reported changes in weight gain. The largest number of sportsactive female students practiced basic exercises for body shaping, relaxation and stretching (89.2%) and strength exercises with own body weight as load intensity (82.4%). Accordingly, it is also necessary to find possible ways, in order to raise awareness of the importance of maintaining their sports and healthy living habits. This primarily refers to maintaining their healthy physical condition, which is also related to their eating habits, as well as preventing the possible occurrence of undesirable health conditions. Such different approaches may apply to all future pandemic conditions, or similar life-threatening conditions.